Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/14651858.cd008552.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for increasing fruit and vegetable consumption in children aged five years and under

Abstract: Interventions for increasing fruit and vegetable consumption in children aged five years and under.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 620 publications
1
7
0
Order By: Relevance
“…A recently published Cochrane review on interventions for increasing fruit and vegetable consumption in children ≤ 5 years, concluded that the evidence for effective interventions remains sparse. Child feeding interventions appeared to increase fruit and vegetable intake, but this conclusion was based on very low-quality evidence, the effect sizes were small, and long-term follow-up was required [45]. This is consistent with findings from a recent review including 22 home-based and community-based interventions aiming to increase vegetable intake in children between 2 and 12 years [46].…”
Section: Discussionsupporting
confidence: 66%
“…A recently published Cochrane review on interventions for increasing fruit and vegetable consumption in children ≤ 5 years, concluded that the evidence for effective interventions remains sparse. Child feeding interventions appeared to increase fruit and vegetable intake, but this conclusion was based on very low-quality evidence, the effect sizes were small, and long-term follow-up was required [45]. This is consistent with findings from a recent review including 22 home-based and community-based interventions aiming to increase vegetable intake in children between 2 and 12 years [46].…”
Section: Discussionsupporting
confidence: 66%
“…A recently published Cochrane review on interventions for increasing fruit and vegetable consumption in children ≤5 years including 50 trials ( n = 10,267), concluded that the evidence for effective interventions to increase eating of fruit and vegetables remain sparse. Child feeding interventions appeared to increase vegetable intake by children, but this conclusion was based on very low-quality evidence, the effect sizes were small, and long-term follow-up was required [54]. In our study children in the intervention group had a higher times-per-day score for servings of fruit/vegetables and for number of vegetables tasted.…”
Section: Discussionmentioning
confidence: 69%
“…However, in comparison to standard curriculum-based nutrition education (for example, a lesson in the classroom on the nutrients in fruits), experiential learning in a school garden has been found to have a greater influence on children’s consumption/energy intake and increasing nutritional knowledge [41]. Children are more willing to try foods after involvement in the growing, preparation and/or cooking of that food, and consumption and skills increases in the short term [42,43]. A comprehensive approach to improving food preparation, knowledge and cooking skills, such as that found in Jamie’s Ministry of Food programme [44], appears to be the most promising for improving community dietary quality.…”
Section: Discussionmentioning
confidence: 99%